In vitro plant regeneration from leaf explants of Withania somnifera (L) Dunal (Ashwaganda) - an important medicinal plant - Kumar, Owk Aniel; Jyothirmayee, Geddam; Tata, Sape Subba (Research in Biotechnology, 2011)
Withania somnifera (L) Dunal (Ashwaganda) is a Solanaceous herb having numerous medicinal values widely used in traditional Ayurvedic drug preparations. An efficient protocol for in vitro plant regeneration via direct adventitious shoot proliferation from leaf explants of Ashwaganda is developed. MS medium containing 1.5mg/l BAP and 1.5mg/l IAA was found to be the best medium for maximum in vitro response i.e., 100(% shooting) and 68(shoots/explant). An improved in vitro shoot bud elongation and rooting was achieved on MS medium fortified with 0.15mg/l GA3 and 5mg/l IBAÃ‚Â  respectively. Rooted plants were hardened and transplanted in earthen pots and were showed 80-90% survival during transplantation.